Circulating bile acid profile characteristics in PCOS patients and the role of bile acids in predicting the pathogenesis of PCOS - Yu, Jie; Zhang, Yi; Zhu, Yuchen; Li, Yushan; Lin, Siyu; Liu, Wei; Tao, Tao (Frontiers in Endocrinology, 2023)
The metabolic profile of bile acids metabolic profile and their potential role as biomarkers of in the pathogenesis of polycystic ovary syndrome (PCOS) have not been thoroughlywell characterized. AssessingThe determination of their predictive value for PCOS will beis of significancesignificant importance.In this study, we enrolled 408 women with PCOS and 204 non-PCOS controls. were enrolled. The serum bile acid profile was measured by using high-performance liquid chromatography-tandem mass spectrometry (LC/MS). We analyzed theThe differences in serum bile acid profiles in between PCOS patients were analyzed byusing the OPLS-DA model. Additionally, we examined The the relationship betweenamong bile acid profiles and parameters related to glucose metabolism and hyperandrogenism was analyzed. ROC analysis was employedused to identify potential biomarkers for PCOS the pathogenesis of PCOS. XGboost was utilizedused for crossvalidation.The bile acid profile was found to be altered in PCOS patientswas altered in PCOS. Specifically, the primary Primary and secondary unconjugated bile acid fractions were significantly higher in the PCOS population. We identified fiveFive most significantly different bile acid metabolite candidates were recognizedthat exhibited the most significant differences between PCOS and non-PCOS controls in PCOS and non-PCOS controls. DCA was associated with deposition index, fasting and postprandial insulin but was influenced by testosterone. CDCA and LCA combined with testosterone showed potential as biomarkers could be used as biomarkers for the pathogenesis of PCOS.Circulating The circulating bile acid profile undergoes changes in PCOS. DCA is associated with deposition index, fasting and postprandial insulin and its level is influenced by 2 This is a provisional file, not the final typeset article testosterone. CDCA and LCA combined with testosterone have the potential to serve as biomarkerscan be used as biomarkers for the pathogenesis of PCOS.